Age, Pain Intensity, Values-Discrepancy, and Mindfulness as Predictors for Mental Health and Cognitive Fusion: Hierarchical Regressions With Mediation Analysis - Edwards, Darren J. (Frontiers in Psychology, 2019)
Background: Several studies have confirmed that higher levels of psychological flexibility predict better functioning for those suffering with chronic pain. However, few studies have investigated the role of the individual components of psychological flexibility within a chronic pain population in relation to aging specifically and the related indirect mediational processes. Aims: The present study aimed to compare how age, pain intensity, mindfulness, and values-discrepancy predicted mental health and cognitive fusion separately. It also explored the indirect process relations through the use of a mediated analysis. Method: 233 participants completed an online survey which included demographical questions as well as the following questionnaires; Short Form McGill Pain Questionnaire (SF-MPQ); General Health Questionnaire 12; Cognitive Fusion 7-Item Questionnaire (CFQ-7); Mindfulness Attention Awareness Scale (MAAS); and the Chronic Pain Values Inventory (CPVI). The relationships from the responses of the questionnaires and demographics were then analysed through two hierarchical regression models followed by further mediation analysis. Results: In the first model, values-discrepancy, pain intensity, and mindfulness all predicted mental health, but age did not. However, age did account for a significant portion of the variance in the second model when cognitive fusion was used as the dependent measure (DV). It was also found that cognitive fusion mediated the relationship between age and mental health. Conclusions: These results are discussed within the context of using indirect process relations of psychological flexibility and third wave therapies such as Acceptance and Commitment Therapy (ACT) for a chronic pain population.